Boundless - Hand, Cynthia, 1978- (Hand, Cynthia, 1978- Unearthly novel., 2013)
"As the battle against the Black Wings and their minions looms on the horizon, part-angel Clara Gardner is finally ready to fulfill her destiny, even though she knows she may have to make the ultimate sacrifice"--Provided by publisher.